Human infection with a novel, highly pathogenic avian influenza A (H5N6) virus: Virological and clinical findings. Issue 1 (January 2016) - Pan, Ming; Gao, Rongbao; Lv, Qiang; Huang, Shunhe; Zhou, Zhonghui; Yang, Lei; Li, Xiaodan; Zhao, Xiang; Zou, Xiaohui; Tong, Wenbin; Mao, Suling; Zou, Shumei; et al.
Summary: Background and objectives: Severe infection with avian influenza A (H5N6) virus in humans was identified first in 2014 in China. Before that, it was unknown or unclear if the disease or the pathogen affected people. This study illustrates the virological and clinical findings of a fatal H5N6 virus infection in a human patient. Methods: We obtained and analyzed the clinical, epidemiological, and virological data from the patient. Reverse transcription polymerase chain reaction (RT-PCR), viral culture, and sequencing were conducted for determination of the causative pathogen. Results: The patient, who presented with fever, severe pneumonia, leucopenia, and lymphopenia, developed septic shock and acute respiratory distress syndrome (ARDS), and died on day 10 after illness onset. A novel reassortant avian-origin influenza A (H5N6) virus was isolated from the throat swab or trachea aspirate of the patient. The virus was reassorted with the HA gene of clade 2.3.4.4 H5, the internal genes of clade 2.3.2.1 H5, and the NA gene of the H6N6 avian virus. The cleavage site of the HA gene contained multiple basic amino acids, indicating that the novel H5N6 virus was highly pathogenic in chicken. Conclusions: A novel, highly pathogenic avian influenza H5N6 virus with a backbone of H5N1 virus acquired from the NA gene from the H6N6 virus has been identified. It caused human infection resulting in severe respiratory disease.